Pendampingan Pembelajaran Bahasa Inggris melalui Contextual Teaching and Learning pada Orang Tua Murid - Handayani, Sri; Riyani, Riyani; Charista, Fhara Dwika Feby (LPPM Universitas Flores, 2022)
Giving guidance to young learners needs a specific strategy that fixes to their needs and world. This social service was conducted from May up to June for all parents who jlin in the organization of teachers and parents in SDIT Alif Smart Surakarta. We have three methods in conducting this activity: (1) Need Analysis, which was done by interviewing parents about their way of accompanying their children in learning English at home, and (2) Socialization about contextual teaching and learning in learning English. It was done by giving material explanation about the notion, steps, and implementation of contextual teaching and learning in learning English at home in accordance to their daily life; and (3) Feedback. This was done by giving feedback about the implementation of contextual teaching and learning in daily life English at home. At first, we coordinated the activity. And secondly, there’s a meeting to encourage all members to have motivation besides giving material for them. The material is all about the implementation of contextual teaching and learning in guiding children to learn English at home. In fact, we discussed how to help all children to learn English and deal with their daily life. There are also questions and answers about how to guide children to learn English effectively and how to solve problems in learning English.